Conversion to Hip Arthroplasty After Cut-out Complication of Proximal Femoral Nailing (PFN) in Pertrochanteric Fractures - Abdullah Merter; Kerem Başarır; Hakan Kocaoğlu; Mustafa Onur Karaca; Emre Anıl Özbek; Mahmut Kalem (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:A failed intertrochanteric fixation often leads to functional disability and pain. The most commonly observed complication is “cut-out”, which frequently requires hip arthroplasty in the subsequent period. In this study, we aimed to compare the results of total hip arthroplasty (THA) and hemiarthroplasty (HA) after cut-out complication of proximal femoral nailing (PFN).Materials and Methods:Forty patients who were treated with THA (20 patients) and HA (20 patients) due to cut-out complication following PFN were included in our retrospective study. Age, gender, classification of the pertrochanteric fracture (AO/OTA classification), time to arthroplasty surgery, operative time, total blood loss, and complications were reviewed. The clinical results were evaluated by the ambulatory status, Harris hip score (HHS) and visual analog scale (VAS) score at the second year follow-up.Results:The amount of blood loss and the operative time were significantly higher in the THA group (p=0.001). Post-operative second year VAS score and HHS were similar in both groups (p=0.989 and p=0.820, respectively). There was no significant difference between the two groups in terms of complications rate (p=0.294).Conclusion:Converting to hip arthroplasty is a successful choice in the treatment of cut-out complications following PFN. Both THA and HA groups had similar clinical results, with the HA group being more advantageous regarding cost, operative time, amount of blood loss, and rate of infection. However, the only valid option for those with acetabular defects during cut-out is THA.